Modulating Cu+ distribution on the surface of Ce-doped CuO composite oxides for SO2-resistant NH3-selective catalytic reduction of NO. Issue 31 (28th March 2017) - Xing, Mengmeng; Sun, Qian; Zeng, Chun; Wang, Huize; Zhao, Dan; Zhang, Ning; Hong, Sanguo
Abstract : Ce dopping in CuO crystalline led to the distinguished existence and modulated distribution of Cu + on the surface of samples, which was responsible for the outstanding SO2 -resistant NH3 -SCR-NO performance. Abstract : A series of (CeO x ) m CuO composite oxides with different Ce/Cu molar ratios ( m ) were prepared by co-precipitation for ammonia-selective catalytic reduction of NO (NH3 -SCR-NO) in the absence and presence of SO2 . Through X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), H2 -temperature programmed reduction (H2 -TPR), and NH3 -temperature programmed desorption (NH3 -TPD) characterization, it was demonstrated that the prepared samples were featured by distinguished Cu + distributions on the surface of the Ce-doped CuO composite structure, indicating a special interaction or synergistic effect present in the samples. The modulated distributions of Cu + achieved by adjusting the Ce/Cu molar ratio were found to be crucial for optimizing the redox ability and acid feature among the samples. The outstanding SO2 -resistant NH3 -SCR-NO performance (NO conversion close to 100% in temperature window of 250–350 °C under 200 ppm SO2 -presence) was observed on (CeO x )0.25 CuO which possessing the highest Cu + distribution, indicating the significant dependence of Cu + distribution in Cu-based catalysts on enhancing catalytic performance for NH3 -SCR-NO. These results also suggested that the distinguished synergistic effect among binary component Cu-based catalysts should be considered as an important factor to govern the performance of NH3 -SCR-NO x, which could be inferred as important clues to innovate more efficient catalysts for NH3 -SCR-NO x, as well as other heterogeneous catalysis applications based on Cu-catalysts.